If it's not what You are looking for type in the equation solver your own equation and let us solve it.
d-4=19/d=15
We move all terms to the left:
d-4-(19/d)=0
Domain of the equation: d)!=0We add all the numbers together, and all the variables
d!=0/1
d!=0
d∈R
d-(+19/d)-4=0
We get rid of parentheses
d-19/d-4=0
We multiply all the terms by the denominator
d*d-4*d-19=0
We add all the numbers together, and all the variables
-4d+d*d-19=0
Wy multiply elements
d^2-4d-19=0
a = 1; b = -4; c = -19;
Δ = b2-4ac
Δ = -42-4·1·(-19)
Δ = 92
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}$$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}$
The end solution:
$\sqrt{\Delta}=\sqrt{92}=\sqrt{4*23}=\sqrt{4}*\sqrt{23}=2\sqrt{23}$$d_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(-4)-2\sqrt{23}}{2*1}=\frac{4-2\sqrt{23}}{2} $$d_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(-4)+2\sqrt{23}}{2*1}=\frac{4+2\sqrt{23}}{2} $
| F(x)=1/2x2-(1/4x+3) | | -25=4x-1 | | 5x+5=7x+-9 | | -11(4+x)=121 | | 180=x+30÷3 | | 5x+3=7x+-11 | | 2x^2+13x=20 | | 3(2/3x+6)-2x=0 | | u+65=5u+29 | | 24=5-6u | | 28+28b=35+21 | | -3+m/14=-2 | | 10=45-s | | 4(3a-4)=56a | | 14z+42=10z+58 | | (100-2x^2)/((100-x^2)^(1/2))=0 | | 8y-7/5=4y-1/3 | | 5/2×v+4=4/5×v-3/5 | | 6(6x-1)-3=171 | | 1/2x^2+3=75 | | -5m+8=-4m+3 | | (2x–8)(x+7)=0 | | x=-7+1/3 | | 2x–8)(x+7)=0 | | 5/2v+4=4/5v-3/5 | | 13+3h=82 | | -(n+1)-5(3-n)=1+n+1-3n* | | 4+p/4=-1 | | 3x+11=-11 | | 10b-76=6b | | 82=w+34 | | (x^2)+x+18=90 |